PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI INSTITUT SAINS DAN TEKNOLOGI TD. PARDEDE MEDAN - JOSLEN SINAGA; Anton Sinaga (JURNAL PROINTEGRITA, 2018)
Employee performance is the work of employees that is reflected in how to plan, implement and assess the service process. Factors suspected of influencing performance are factors of leadership style and work discipline. This study aims to determine the effect of leadership style and work discipline partially and simultaneously on the performance of employees of the TD Institute of Science and Technology. Pardede Medan. The population of this study amounted to 45 employees. Considering the number of population is not up to 100 people, this study uses the entire population to be a sample (total sampling). Thus, the sample size of this study was 45 people. Data collection techniques in this study are questionnaires, interviews and documentation studies. While the data analysis technique used is the classic assumption test, multiple regression, t test, F test and coefficient of determination. The results showed that leadership style variables had a positive and significant effect on the performance of ISTP TD employees. Pardede Medan, with t-count values for leadership style variables of 7.941> 2.018 and a significance level of 0.000 <0.05. The better the leadership style, the higher the employee's performance. Work discipline variables have a positive and significant effect on the performance of ISTP TD employees. Pardede Medan, with t-count values for the working discipline variables of 4.475> 2.018 and a significance level of 0.000 <0.05. The higher the work discipline, the higher the employee's performance. Variables of leadership style and work discipline simultaneously have a positive and significant effect on the performance of ISTP TD employees. Pardede Medan, with an Fcount of 273,350> F table of 3,220 and a significance level of 0,000 <0,05. As much as 92.90% of the variation in employee performance can be explained by changes in the variables of leadership style and work discipline simultaneously, while the remaining 7.10% is explained by other factors, namely motivation, work facilities and work environment.